Development of Web Learning to Improve Learning Outcomes in IPAS Subject of Plant Body Parts Class IV in Elementary School (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research aims to develop web learning to improve student learning outcomes in the Science subject matter on Plant Parts for Class IV at SDN 4 Bungbulang, Garut Regency, for the 2024-2025 academic year. The method used is the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Web learning is designed to be interactive, easily accessible, and integrated with various Google applications. The research results show that the use of Google Sites-based web learning can significantly improve student learning outcomes. Regression analysis yielded a linear equation: Ŷ = 35.505 + 0.729X. Furthermore, hypothesis testing to assess significance yielded a calculated t-value of 4.428, which is greater than the t-table value of 1.708, meaning H0 is rejected and H1 is accepted. This indicates that there is an influence of Google Sites-based web learning media on student learning outcomes. To see the extent of the influence of variable X, the R-squared value of 0.440 is observed, meaning that Google Sites-based web learning media has a 44.0% effect on student learning outcomes. Therefore, the Google Sites-based web learning product is suitable for use and development in learning.